Proximity and gaze influences facial temperature: a thermal infrared imaging study - Ioannou, Stephanos; Morris, Paul; Mercer, Hayley; Baker, Marc; Gallese, Vittorio; Reddy, Vasudevi (Frontiers in Psychology, 2014)
Direct gaze and interpersonal proximity are known to lead to changes in psycho-physiology, behavior and brain function. We know little, however, about subtler facial reactions such as rise and fall in temperature, which may be sensitive to contextual effects and functional in social interactions. Using thermal infrared imaging cameras 18 female adult participants were filmed at two interpersonal distances (intimate and social) and two gaze conditions (averted and direct). The order of variation in distance was counterbalanced: half the participants experienced a female experimenter's gaze at the social distance first before the intimate distance (a socially “normal” order) and half experienced the intimate distance first and then the social distance (an odd social order). At both distances averted gaze always preceded direct gaze. We found strong correlations in thermal changes between six areas of the face (forehead, chin, cheeks, nose, maxilliary, and periorbital regions) for all experimental conditions and developed a composite measure of thermal shifts for all analyses. Interpersonal proximity led to a thermal rise, but only in the “normal” social order. Direct gaze, compared to averted gaze, led to a thermal increase at both distances with a stronger effect at intimate distance, in both orders of distance variation. Participants reported direct gaze as more intrusive than averted gaze, especially at the intimate distance. These results demonstrate the powerful effects of another person's gaze on psycho-physiological responses, even at a distance and independent of context.